A Kaldor Matching Model of Real Wage Declines - Michael Sattinger (Institute for the Study of Labor (IZA), 2001)
A model linking macroeconomic phenomena and income distribution in balanced growth equilibria is developed as a variant to the Kaldor model of factor shares. It departs from the original Kaldor model in assuming equal savings rates and production determined by a matching process between workers and jobs. Macroeconomic equilibrium (national savings equal to investment) determines the ratio of jobs to employment and the ratio of unemployed to vacancies. Competitive microeconomic behavior then determines the wage and interest rates. Changes in the ratio of national debt to employment have real effects on factor prices. Implications for effects of taxes and unemployment benefits are derived. The model explains recent declines in real wages relative to productivity.
Keywords: D33; H2; E1; J31; 330; Kaldor; real wage; interest rate; national debt; unemployment benefits; efficient taxation; matching; factor prices; Verteilungstheorie; Wirtschaftswachstum; Matching; Faktorpreis; Lohnbildung; Öffentliche Schulden; Reallohn; Theorie